2012
DOI: 10.1128/aac.05166-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Resistance Profile of the Hepatitis C Virus NS3 Protease Inhibitor BI 201335

Abstract: The in vitro resistance profile of BI 201335 was evaluated through selection and characterization of variants in genotype 1a (GT 1a) and genotype 1b (GT 1b) replicons. NS3 R155K and D168V were the most frequently observed resistant variants. Phenotypic characterization of the mutants revealed shifts in sensitivity specific to BI 201335 that did not alter susceptibility to alpha interferon. In contrast to macrocyclic and covalent protease inhibitors, changes at V36, T54, F43, and Q80 did not confer resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 29 publications
7
56
0
Order By: Relevance
“…This finding, coupled with the low fold changes in sensitivity associated with several substitutions that confer resistance to other NS5B polymerase inhibitors, suggests that deleobuvir may have an enhanced barrier to resistance compared with other members of this class. Importantly, RAVs that emerged in this trial were different from those reported with NS3/4A PIs (30,31), reflecting their nonoverlapping resistance profiles. PK assessments demonstrated supraproportional plasma exposure and progressive reductions in clearance with increasing dose of deleobuvir.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This finding, coupled with the low fold changes in sensitivity associated with several substitutions that confer resistance to other NS5B polymerase inhibitors, suggests that deleobuvir may have an enhanced barrier to resistance compared with other members of this class. Importantly, RAVs that emerged in this trial were different from those reported with NS3/4A PIs (30,31), reflecting their nonoverlapping resistance profiles. PK assessments demonstrated supraproportional plasma exposure and progressive reductions in clearance with increasing dose of deleobuvir.…”
Section: Discussionmentioning
confidence: 54%
“…The most common types of event (mild to moderate GI, nervous system, and skin/subcutaneous reactions) have also been reported with PIs (7,10,12,20,30,32,33) and with other NS5B polymerase inhibitors under development (alone or in combination regimens) (34)(35)(36)(37). Baseline and follow-up electrocardiographs revealed no clinically relevant findings.…”
Section: Discussionmentioning
confidence: 99%
“…In patient B, the Q80L mutation is detectable via pyrosequencing at low levels pre-Faldeprevir therapy and becomes dominant post-therapy. Interestingly, Q80L mutations do not render replicons resistant to a range of PIs (Lenz et al, 2010) and are not implicated in Faldeprevir resistance in vitro (Lagace et al, 2012) or in vivo (Berger et al, 2013). Our data demonstrate the Q80L mutation is selectively neutral with respect to viral replication and does not confer cross-resistance to Boceprevir or Teleprevir.…”
Section: Discussionmentioning
confidence: 72%
“…Drug sensitivity assays showed that Q80K resulted in mean reductions in simeprevir susceptibility of 9.5-fold and 14.0-fold in genotype 1a and 1b replicon assays, respectively ( Fig. 2) (29). It should be noted that since this variant occurs almost exclusively in HCV genotype 1a clinical isolates, it is more relevant to also assess its impact on in vitro drug susceptibility in a genotype 1a background.…”
Section: Discussionmentioning
confidence: 99%